Error Correction Code in Optical Fiber - Abdul-Alwahab, Mohammed; Abdul-Hassan Gitaffa, Sabah; Adnan Kadhim, Raidh (Journal of Engineering and Sustainable Development, 2007)
Error correction codes have been successfully implemented in wire-line and wireless communication to offer error-free transmission with high spectral efficiency. The drive for increased transmission capacity in fiber-optic links has drawn the attention of coding experts to implement forward error correction (FEC) for optical communication systems in the recent past. Particularly, the ITU-T G.975 recommended Reed-Solomon RS (255, 239) code, is now commonly used in most long-haul optical communication systems. It was shown that the code offers a net coding gain of around 4.3 dB for an output bit-error rate of 10-8 after correction. The Monte-Carlo simulation and theoretical performance analysis for the RS (255,239) code with 6.7% redundancy were presented for a completely random distribution of errors over an additive white Gaussian noise (AWGN) channel with BPSK signaling and hard decision decoding. In addition, net coding gain comparison was done between the ITU-T G.975 standard and that offered by the RS (255, 247) and RS (255, 223) codes with 3.2% and 14.3% redundancy respectively.